Evaluation of HbA1c and fasting plasma glucose for the diagnosis of post-transplant diabetes mellitus and prediabetes in renal transplant recipients (Journal of Fatima Jinnah Medical University, 2019)
Background: Diabetes mellitus after renal transplantation (PTDM) is a frequent complication and if not timely diagnosed may result in life-threatening microvascular complications. Fasting plasma glucose (FPG) test is considered preliminary screening tool while oral glucose tolerance test (OGTT) is a ‘benchmark test’ for the screening of DM and prediabetes in PTDM. HbA1c test is also now being considered as a most convenient diagnostic tool for Type 2 diabetes mellitus and prediabetes. Therefore, current study was undertaken to evaluate HbA1c and FPG tests for the diagnosis of diabetes and prediabetes by taking OGTT as a gold standard.Patients and methods: In this prospective study, total 40 renal transplant recipients were recruited from Jinnah and Mayo Hospitals Lahore from January to August 2012. The participants aged ≥18 years who underwent renal transplants more than 3 months ago with no prior history of diabetes mellitus were included. Blood samples were obtained for FPG, OGTT and HbA1c tests according to standard guidelines. Based on ADA thresholds of OGTT, patients were categorized into three groups: 1) DM; 2) prediabetes, and 3) normal plasma glucose levels.Results: Hyperglycemia was seen in 22 (55%) patients including 6 (15%) with PTDM and 16 (40%) with prediabetes based on OGTT. High value of AUC of FPG (0.8469 p
Keywords: PTDM; Prediabetes; Transplantation; HbA1C; FPG